Method for Nanomodulation of Metallic Thin Films Following the Replica-Antireplica Process Based on Porous Alumina Membranes - Escrig-Murua, J; Casagrande-Denardin, J (Elsevier B.V., 2017)
In this paper we have introduced a method for modulation of metallic thin films by sputtering of metals on anodized aluminum templates. Using a high deposition rate during deposition of the non-magnetic metal on the Al pattern, we have separated the two metallic surfaces and, thus, imprinted a pattern of nanohills on a non-magnetic metallic film, such as Au, Ag or Cu. The morphology of the nanostructured metallic films was determined by scanning electron microscopy. Thus, we have confirmed that the ordering degree of the Al template remained after the replication process. Additionally, and as an example of use of these films, we have prepared Supermalloy thin films deposited by sputtering onto these nanostructured non-magnetic metals. The room temperature magnetic behavior of these thin films is also studied. Interestingly, we have found that when the external magnetic field is applied out of plane of the substrate, the coercivity increases linearly as we increase the radius of the nanohills. These soft magnetic films can open new opportunities for magnetic field sensor applications. © 2016 Elsevier B.V.